Development of a novel and efficient H2O2 sensor by simple modification of a screen printed Au electrode with Ru nanoparticle loaded functionalized mesoporous SBA151. Issue 43 (14th May 2015) - Hazra, Subhenjit; Joshi, Hrishikesh; Ghosh, Barun Kumar; Ahmed, Asif; Gibson, Timothy; Millner, Paul; Ghosh, Narendra Nath
<x xml:space="preserve">Abstract</x> A novel and efficient electrochemical sensor has been developed to quantitatively measure H2O2 concentration by cyclic voltammetry.